2019
DOI: 10.15689/ap.2019.1804.18917.05
|View full text |Cite
|
Sign up to set email alerts
|

Trabalho e Bem-Estar: Evidências da Relação entre Burnout e Satisfação de Vida

Abstract: Esse estudo visa investigar a relação entre Burnout e satisfação de vida em trabalhadores brasileiros pelo modelo teórico Job Demands-Resources (JDR), da Psicologia Positiva. Foram testadas as associações entre Burnout e demandas e recursos de trabalho, satisfação de vida e sintomas depressivos, em 986 participantes das cinco regiões brasileiras, entre 18 e 89 anos (M=39, DP=11,1), sendo 87,2% de mulheres. Os resultados demonstram que Burnout prediz sintomas depressivos e é consequente de altas demandas e baix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 26 publications
3
4
0
14
Order By: Relevance
“…Finally, regarding the comparison among Italian data and the seven countries included in the cross-national study [ 48 ], our sample presented relatively higher burnout scores as compared to Finland, Austria, Germany, and The Netherlands. As widely established in other countries [ 49 , 50 , 51 ], the empirical evidence provided in the current study strongly concurs in proposing that even in the Italian context, the BAT may offer both a conceptually robust and empirically reliable tool for measuring burnout in work settings.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Finally, regarding the comparison among Italian data and the seven countries included in the cross-national study [ 48 ], our sample presented relatively higher burnout scores as compared to Finland, Austria, Germany, and The Netherlands. As widely established in other countries [ 49 , 50 , 51 ], the empirical evidence provided in the current study strongly concurs in proposing that even in the Italian context, the BAT may offer both a conceptually robust and empirically reliable tool for measuring burnout in work settings.…”
Section: Discussionsupporting
confidence: 85%
“…In line with international results on the BAT [ 48 , 49 , 50 , 51 ], this study showed that the BAT represents a reliable, valid, and free to use alternative to the MBI-GS in the Italian context. It is crucial to have a free to use tool that allows researchers to compare data from different countries, sectors, and professional roles.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Observa-se, portanto, um crescente número de afastamentos por saúde e, em paralelo, o acréscimo da síndrome na Classificação Internacional de Doenças, conforme proposta da OMS 20 . Faz-se importante destacar que o Burnout, enquanto desfecho negativo na relação da pessoa com seu trabalho, pode apresentar diferentes manifestações e caminhos, seja em função das características da organização e do/no ambiente de trabalho, seja em relação às variáveis socioculturais 19 .…”
Section: Iissn 2318-0404unclassified